EVOLUTION OF OROGENIC WEDGES AND CONTINENTAL PLATEAUX: INSIGHTS FROM CRUSTAL THERMAL-MECHANICAL MODELS OVERLYING SUBDUCTING MANTLE LITHOSPHERE - Vanderhaeghe O.; Medvedev S.; Fullsack P.; Beaumont C.; Jamieson R.A. (My University, 2003)
The links between an early phase of orogenesis, when orogens are commonly wedge shaped, and a later phase, with a plateau geometry, are investigated using coupled thermal-mechanical models with uniform velocity subduction boundary conditions applied to the base of the crust, and simple frictional-plastic and viscous rheologies. Models in which rheological properties do not change with depth or temperature are characterized by growth of back-to-back wedges above the subduction zone. Wedge taper is inversely dependent on the Ramberg number (Rm; gravity stress/basal traction); increasing convergence velocity or crustal strength produces narrower and thicker wedges. Models that are characterized by a decrease in crustal viscosity from $η c $ to $η b $ with depth or temperature, leading to partial or full basal decoupling of the crust from the mantle, display more complex behaviour. For models with a moderate viscosity ratio, $η b /η c ~ 10-1 $, the crustal wedges have dual tapers with a lower taper in the central region and a higher taper at the edges of the deformed crust. A reduction in the viscosity ratio $(η b /η c ~ 10-2 )$ is sufficient to cause a transition of the central wedge region to a plateau. This transition depends on the basal traction, therefore the thickness of the weak basal layer also affects the transition. Further reduction of the viscosity ratio $(η b /η c ~ 10-4 )$ leads to full basal decoupling and the development of plateaux in all cases considered. In most models, the plateaux grow laterally at constant thickness between characteristic edge peaks associated with the transitions from coupled to decoupled lower crust. Where the crust is fully decoupled, large-scale model geometries for both depth- and temperature-dependent rheologies are similar with gravity-driven flow concentrated in the low-viscosity region. However, strong lateral temperature gradients within these models, controlled by the interaction of horizontal and vertical thermal advection, diffusion and heterogeneous thickening of the radioactive crustal layer, lead to differences in the velocity and deformation fields between the two cases, particularly at the plateau margins. The results suggest that simple depth-dependent viscosity models may be reasonable approximations for describing the large-scale geometry of fully developed plateaux, but that they are not appropriate for describing the internal features of large orogenic systems or the transition from wedge to plateau geometry.
Keywords: CONTINENTAL DEFORMATION; CRUSTAL DEFORMATION; ISOSTASY; OROGENY; RADIOACTIVITY; TOPOGRAPHY; VISCOSITY